Analisis Pendapatan Agroindustri Kerupuk Sagu di Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti (Studi Kasus pada Usaha Mandiri Bunga Mawar) - Ihsan Ramadhan Al-'Afif; Evy Maharani; Eliza Eliza (Jurnal Social Economic of Agriculture, 2022)
This study aims to determine the total cost of production in the sago cracker agroindustry and analyze the income, added value, business efficiency, and the breakeven point (BEP) of the sago cracker agroindustry. This research was conducted at the Mawar Bunga Mandiri Business, which is located in the Tebing Tinggi District, Meranti Islands Regency. The Mawar Bunga Mandiri Business was chosen as the research location because the Mawar Bunga Mandiri Business was one of the independent businesses that already existed at the Department of Industry and Trade of the Meranti Islands Regency and was registered in the promotion building in Tebing Tinggi District, Meranti Islands Regency. The results showed that the total production costs incurred by business actors in one production process were Rp. 259.914. The net income received by business actors in one production process is Rp. 78.086. The added value owned by business actors in one production process is Rp. 21,195/Kg. The value of business efficiency is 1.30, which means every Rp. 1 issued generates revenue of Rp. 1.30 and an income of Rp. 0.30 so that the sago cracker agro-industry business is efficient and profitable so it is feasible to continue. The BEP value of production is 142 units with a BEP cost of Rp. 1,842.598.